2018
DOI: 10.1007/s11912-018-0679-9
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Transplantation for Adult Philadelphia-Negative Acute Lymphoblastic Leukemia in the First Complete Remission in the Era of Minimal Residual Disease

Abstract: Allo-HSCT continues to have a role in the therapy of a selected group of high-risk adult patients with ALL in CR1. Although the clinical significance of MRD has been studied less extensively in adults with ALL than in children, recent studies support its role as the strongest prognostic factor that can identify patients that are unlikely to be cured by standard chemotherapy and benefit from undergoing allo-HSCT. In addition, MRD status both pre- and post-HSCT has been found to correlate directly with the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Consistent with previous studies, [ 14 , 16 20 , 23 , 25 , 64 ] our study showed that patients with post-MRD + suffered higher CIR and poorer survival than post-MRD − patients. In addition, we also found that post-MRD + at different time points was related to a higher incidence of relapse and a lower probability of LFS and OS, which was consistent with the results of Bader et al .…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies, [ 14 , 16 20 , 23 , 25 , 64 ] our study showed that patients with post-MRD + suffered higher CIR and poorer survival than post-MRD − patients. In addition, we also found that post-MRD + at different time points was related to a higher incidence of relapse and a lower probability of LFS and OS, which was consistent with the results of Bader et al .…”
Section: Discussionsupporting
confidence: 93%
“…Residual leukemia cells in patients are the main cause of disease relapse. The OS and PFS for no remission (NR) patients are significantly lower than those for CR patients, and the cumulative relapse rate is also significantly higher than that of remission patients [9,10]. However, even if the patient is in CR status, the MRD may be detected in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first immunotherapies used for T cell lymphoma and leukemia is allogeneic stem cell transplantation. In allo-HCT the entire hemopoietic and immune system of the patient is substituted with one derived from an HLA-matched donor(45). This strategy has demonstrated to be the only curative option for a subset of TCL(46-48), however treatment-related mortality and late graft versus host complications could impact long-term quality of life (46-48).…”
Section: Immunotherapeutic Strategies For T Cell Leukemia and Lymphomamentioning
confidence: 99%